(untitled) (Global Journal of Management and Business Research, 2021)
With the development of globalization, the number of international students in Chinese colleges will continue to grow, and the education of international students has gradually become an important part of the domestic higher education system. Facing the group of international students in China, its complicated cultural backgrounds and individual differences further increase the difficulty of school management. Therefore, colleges need to start from the perspective of cross-cultural management to strengthen the management of international students, improve and innovate the management system of domestic universities. In this case, schools can reduce the cultural anxiety of international students and improve the cross-cultural awareness of managers, as well as create a better campus environment. In a long run, schools can then create a good environment conducive to the reform, innovation, and development of domestic higher education, and promote the rapid and highquality development of national education.